O trabalho da coordenação pedagógica e a formação continuada em serviço de professores alfabetizadores: o que dizem as pesquisas? - Barbosa, Priscila Ishiki [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Associated with the aging process, as well as with population aging, the increased incidence of cardiovascular diseases (CVDs) stands out. Considering the different cardiovascular risk (CR) factors, the interest in establishing relationships of the protective role of physical exercise in health problems is growing, as well as in the regulation of the oxidative profile. However, few studies assess the level of physical fitness associated with the chronic response to exercise in the adult and elderly population. In this sense, the present study aimed to investigate the behavior of the CR and oxidative profiles in response to increased physical fitness. A total of 115 adults and elderly people, aged between 50 and 79 years, who underwent physical, hemodynamic, hemodynamic, anthropometric and biochemical evaluations were selected to seek to establish relationships between the different factors of CR. The intervention protocol consisted of participation in physical exercise programs for 12 weeks, with evaluations being carried out before and after the intervention. Participants were classified according to the general functional fitness index (GFFI), into three groups (G1: very weak and weak; G2: regular; G3: good and very good), according to the CR (high CR, CR moderate and low RC) and according to the response to the intervention (increased GFFI and maintained GFFI). The t test of independent samples, t test of paired samples and analysis of variance (ANOVA two-way) were performed, using Tukey's post-test to detect differences (p<0.05) between groups and moments (pre and post). Comparisons between groups were performed using the chi-square test (χ2) and Pearson's Correlation Coefficient analysis between RC and GFFI in the pre and post moments. The response of IAFG groups to the intervention period demonstrates that individuals with lower physical conditioning have a greater response to the increase in NO in response to the increase in IAFG. While individuals with better physical conditioning present reduction in the plasma concentration of pro-oxidant substances, such as thiobarbituric acid reactive substances (TBARS) and carbonyl proteins, thus reflecting a better blood pressure control. In addition, it is concluded that greater physical conditioning contributes to a better CR profile. However, despite observing the change in the CR groups in the post moment, when considering the level of physical conditioning, no differences were observed in the CR profile considering the response to physical training. The study findings allow establishing relationships between physical conditioning, CR and the chronic responses of CR factors to intervention.

A coordenação pedagógica é responsável por uma das principais possibilidades de formação continuada, especialmente a que ocorre em serviço. A formação continuada em serviço é de fundamental importância para os profissionais da educação na instituição escolar, pois, ao se depararem em seu cotidiano com questões e contradições podem refletir coletivamente sobre elas, trazendo novas perspectivas e soluções específicas para aquela instituição. O coordenador pedagógico, dentre suas atribuições, tem o papel de fomentar, acolher e formar os professores com base nas especificidades de seu espaço de atuação. Considerando a importância da coordenação pedagógica nos aspectos formativos, procuramos levantar neste trabalho de conclusão de curso, teses e dissertações sobre a formação continuada realizada pelo coordenador pedagógico durante o serviço, porém, dentro de um recorte de professor: o alfabetizador que atua nos Anos Iniciais do Ensino Fundamental. Essa escolha parte da importância também do trabalho do alfabetizador na aquisição escrita da língua materna como possibilidade de desencadear ações críticas e transformadoras na realidade. Considera-se que todo professor deva ser bem formado e receber ações formativas em serviço, mas, dada a essencialidade dos primeiros anos escolares, o professor alfabetizador demanda maior atenção por parte da coordenação pedagógica. Assim, na presente pesquisa realizamos um levantamento bibliográfico de caráter quali-quantitativo de 65 teses e dissertações, sendo 55 dissertações e 10 teses, dentre as quais foram escolhidas 16 produções para análise mais detalhada por tratarem especificamente da formação em serviço para professores alfabetizadores por meio dos coordenadores pedagógicos. Esse levantamento na Biblioteca Digital Brasileira de Teses e Dissertações (BDTD), a base digital escolhida, trouxe como considerações finais a urgência de pesquisas bibliográficas em Educação sobre a temática, analisando as influências de projetos e instâncias superiores - Estado e Federação - na formação continuada em serviço e as suas principais tendências pedagógicas utilizadas.
The work of pedagogical coordination and training continued in service of literacy teachers: what say the polls?
Keywords: Teacher education; Literacy; Professores-Formação; Coordenação pedagógica; Alfabetização